2021
DOI: 10.1111/eci.13560
|View full text |Cite
|
Sign up to set email alerts
|

Serum alkaline phosphatase is associated with arterial stiffness and 10‐year cardiovascular disease risk in a Chinese population

Abstract: BackgroundSerum alkaline phosphatase (ALP) has been recognized as a biomarker of cardiovascular disease (CVD) risk or mortality, recently. This study aimed to explore the association of ALP with arterial stiffness and 10-year CVD risk. MethodsA total of 12539 participants without CVD who underwent health examinations including serum ALP level were retrospectively analyzed. Arterial stiffness was measured by brachial ankle pulse wave velocity (baPWV) and10-year CVD risk was evaluated by Framingham risk score (F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
1
2
Order By: Relevance
“…The level of PBP in patients with SH was associate with more factors than in euthyroid patients with HTN, namely by gender, hemoglobin, AP levels, which does not contradict the results of other researchers: PBP levels are indirectly associated with AP via arterial stiffness [34,35] and independently associated with anemia [36] and worse metabolic profile in women [37]. Moreover, patients with a combined course of HTN and SH tend to have anemia and liver abnormalities, which makes the effect of hemoglobin and AP levels more noticeable in this category of patients.…”
Section: Discussionsupporting
confidence: 58%
“…The level of PBP in patients with SH was associate with more factors than in euthyroid patients with HTN, namely by gender, hemoglobin, AP levels, which does not contradict the results of other researchers: PBP levels are indirectly associated with AP via arterial stiffness [34,35] and independently associated with anemia [36] and worse metabolic profile in women [37]. Moreover, patients with a combined course of HTN and SH tend to have anemia and liver abnormalities, which makes the effect of hemoglobin and AP levels more noticeable in this category of patients.…”
Section: Discussionsupporting
confidence: 58%
“…However, prior to the present study, the association between serum ALP and Ba-PWV had not been investigated thoroughly, especially in a regular population. In our literature review, we found only one previous study on the association between serum ALP and Ba-PWV in a Chinese population 29 . Although that study also observed a significant relationship between ALP and Ba-PWV, we also observed a specific saturation effect in this relationship.…”
Section: Discussioncontrasting
confidence: 51%
“…In our literature review, we found only one previous study on the association between serum ALP and Ba-PWV in a Chinese population. 29 Although that study also observed a significant relationship between ALP and Ba-PWV, we also observed a specific saturation effect in this relationship. Moreover, we explored the association in further subgroup analyses to obtain new findings that provide insight for the design of further research.…”
Section: Discussioncontrasting
confidence: 40%
“…Mice with endothelial ALP overexpression have been shown to have an increased risk of developing arterial hypertension and compensatory left ventricular hypertrophy [ 76 ] ( Table 1 ). This finding was confirmed by a retrospective study of 12,539 patients without CVD, in which it was observed that elevated ALP levels were independently associated with arterial stiffness and an increased 10-year cardiovascular risk [ 77 ]. Similarly, Perticone et al demonstrated in a study of 500 hypertensive patients without CKD, that elevated ALP values were associated with an alteration in endothelium-dependent vasodilation, an important measure of endothelial dysfunction [ 78 ].…”
Section: Alp and Balp: Vascular Calcification Endothelial Dysfunction...mentioning
confidence: 63%